# Trig

posted by Anonymus

Use Trig identities to verify that sec^4(x)-tan^4(x)=1+2tan^2(x), Only work with one side of the equation

1. agrin04

sec^4(x) - tan^4(x) =
= (1 + tan^2(x))^2 - tan^4(x)
= 1 + 2tan^2(x) + tan^4(x) - tan^4(x)
= 1 + 2tan^2(x)

QED

## Similar Questions

1. ### Trigonometry

Use the trig Identities to find the other 5 trig functions. Problem 7.)Tan(90-x)=-3/8 8.)Csc x=-13/5 9.)Cot x=square root of 3 10.)Sin(90-x)=-.4563 11.)Sec(-x)=4 12.)Cos x=-.2351 I need HELP!
2. ### trig

Prove: sec*4x-tan*4x=1+2tan*2x
3. ### Math

Prove Trig. Identities 1. sec è (sec è - cos è)= tan^2 è 2. tan^2 è (1 + cot^2 è) = sec^2 è
4. ### trig

Verify that each trigonometric equation is an identity tan^2+1/sec Î± =sec Î±
5. ### pre calculus 2

use the fundamental trig. Identities to simplify tan^4x+2tan^2x+1
6. ### Trig

Proving Identities: 2 columns (tan + cot)^2 = sec^2 + csc^2 I'm having trouble breaking down the left side to = the right side.. Any help please
7. ### trig

prove: (tan x + sec x)^2 = 2sec^2 x + 2tan x sec x - 1
8. ### calculus (check my work please)

Not sure if it is right, I have check with the answer in the book and a few integral calculators but they seem to get a different answer ∫ sec^3(x)tan^3(x) dx ∫ sec^3(x)tan(x)(sec^2(x)-1) dx ∫ tan(x)sec(x)[sec^4(x)-sec^2(x)] …
9. ### Trig

Verify each trigonimetric equation by substituting identities to match right hand side of the equation to the hand side of the equation. Please help. -tan^2x+sec^2x=1
10. ### Trig Identities

Prove the following identities: 13. tan(x) + sec(x) = (cos(x)) / (1-sin(x)) *Sorry for any confusing parenthesis.* My work: I simplified the left side to a. ((sinx) / (cosx)) + (1 / cosx) , then b. (sinx + 1) / cosx = (cos(x)) / (1-sin(x)) …

More Similar Questions